Urban public space materials. Maintenance and design? - Manuel Iglesias Campos (On the W@terfront, 2016)
In this paper, certain aspects related to the conservation of materials commonly used in the design of public spaces are analysed and discussed from a starting point of maintenance definition. The main area of discussion is whether materials selection for pavements and urban furniture, and their placement in the designed space, take into account their maintenance needs. Here the definition of maintenance is the cleaning and repair done by municipal services that is always necessary after construction. From certain examples it can be concluded that, in several cases, the form, the organization and the distribution of the different elements within the public space can cause difficulties for its appropriate conservation, giving rise to alterations and consequently having a negative impact on the durability of this space.